2011
DOI: 10.1186/1423-0127-18-93
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of sesamol in inhibiting NF-κB-mediated signaling in platelet activation

Abstract: BackgroundPlatelet activation is relevant to a variety of coronary heart diseases. Our previous studies revealed that sesamol possesses potent antiplatelet activity through increasing cyclic AMP formation. Although platelets are anucleated cells, they also express the transcription factor, NF-κB, that may exert non-genomic functions in platelet activation. Therefore, we further investigated the inhibitory roles of sesamol in NF-κB-mediated platelet function.MethodsPlatelet aggregation, Fura 2-AM fluorescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It also increases cAMP and cGMP levels, expression of endothelial nitric oxide synthase (eNOS) and NO release. In yet another study, Chang et al [12] have further advanced the investigation wherein they found that sesamol (2.5e 25 mM) stimulates cAMP-PKA signaling, subsequently inhibits NF- kB-PLC-PKC cascade, thereby leading to attenuation of Ca 2þ mobilization and inhibition of platelet aggregation. ADP-induced platelet aggregation occurs via the coordinated activation of two G proteinecoupled receptors, P2Y1 and P2Y12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also increases cAMP and cGMP levels, expression of endothelial nitric oxide synthase (eNOS) and NO release. In yet another study, Chang et al [12] have further advanced the investigation wherein they found that sesamol (2.5e 25 mM) stimulates cAMP-PKA signaling, subsequently inhibits NF- kB-PLC-PKC cascade, thereby leading to attenuation of Ca 2þ mobilization and inhibition of platelet aggregation. ADP-induced platelet aggregation occurs via the coordinated activation of two G proteinecoupled receptors, P2Y1 and P2Y12.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is also used in the production of drugs for depression [11]. Recent studies have reported that sesamol in the concentration range 2.5e100 mM inhibits platelet aggregation by increasing the rate of cyclic AMP (cAMP) formation and attenuating the Nuclear Factor-kappa B (NF-kB) signaling events, thus depicting it to be an anti-thrombotic and cardioprotective compound [8,12]. However, the present study sought to demonstrate the effect of sesamol at higher concentrations on platelet functions, which is unknown hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the last sentence of the abstract, it is written "On the basis of these data, NF-κB is also identified as a new target to dampen unwanted platelet activation." The second article of Spinelli et al is just an editorial comment of the article published by Gambaryan et al 2 More important still, there is no mention of 7 other articles, [5][6][7][8][9][10][11] including a pioneer work from our group, 5 describing an opposite effect of NF-κB activation in platelets. In fact, using different strategies (including IkB kinase β knockout mice), these studies show that activation of NF-κB pathway promotes platelet activation.…”
Section: On "Platelets As Cellular Effectors Of Inflammation In Vascularmentioning
confidence: 99%
“…1) has a wide range of biological actions, including: anti-mutagenesis [1]; antioxidant [2]; suppression of neuro-inflammation [3]; inhibition of atherosclerosis progression [4]; inhibition of NF-B in platelet aggregation [5,6]; and, reduction of plasma cholesterol and triacylglycerol levels [7].…”
Section: Introductionmentioning
confidence: 99%